ChemInform Abstract: New Approach Towards the Synthesis of Selenosemicarbazones, Useful Compounds for Chagas′ Disease. Issue 24 (27th May 2016) - Pizzo, Chiara; Faral‐Tello, Paula; Yaluff, Gloria; Serna, Elva; Torres, Susana; Vera, Ninfa; Saiz, Cecilia; Robello, Carlos; Mahler, Graciela
Abstract: Eleven selenosemicarbazones are prepared with low to moderate yields.